Law and the relational self / Jonathan Herring. - Herring, Jonathan (Law in context., 2020)
This book promotes a relational understanding of the self. It explores how law can be transformed by focusing on the promotion and protection of caring relationships, rather than individual rights. This offers a radical and profound re-imagining of what law is about and what it should be trying to do. It moves from the theoretical into offering practical examples of how the law could be developed to enhance relationships, rather than undermine them.